From slave ship to supermax: mass incarceration, prisoner abuse, and the new neo-slave novel - Alexander, Patrick Elliot (Temple University Press, 2018)
Introduction: antipanoptic expressivity and the new neo-slave novel -- Talking in George Jackson's shadow: neoslavery, police intimidation, and imprisoned intellectualism in Baldwin's If Beale Street could talk -- Middle passage reinstated: whispers from the women's prison in Morrison's Beloved -- "Didn't I say this was worse than prison?": the slave ship-Supermax relation in Johnson's Middle passage -- "Tell them I'm a man": slavery's vestiges and imprisoned radical intellectualism in Gaines's A lesson before dying -- Epilogue: the prison classroom and the neo-abolitionist novel